A proximity-labeling-based approach to directly detect mRNA delivery to specific subcellular locations - Alfredo D. Smart; Merryn E. Hughes; Angela Downie Ruiz Velasco; Naoto Hori; Snow Stolnik; Catherine L. Jopling (Molecular Therapy: Nucleic Acids)
Messenger RNA (mRNA) therapeutics show considerable promise but face delivery challenges, as effective cytosolic entry and subsequent translation are normally limited by endosomal entrapment. While various approaches have been used to investigate determinants of effective RNA delivery, these methods tend to be indirect, qualitative, or rely on labeled RNA. There is a need for quantitative approaches that can directly measure mRNA delivery to its functional sites within the cell. Here, we adapted the APEXseq approach for proximity biotinylation and isolation of mRNA at specific subcellular locations. We combined APEX2 labeling with reverse-transcription quantitative PCR to investigate mRNA delivery to the cytoplasm and endoplasmic reticulum, the two major sites of translation, and found it was most effective in the endoplasmic reticulum. We incorporated a biotinylated spike-in RNA to improve existing methodology by allowing normalization of data and optimization of mRNA pull-down conditions. Finally, we combined this method with protein assays to investigate the role of different signal peptides in mRNA delivery to, and translation at, the endoplasmic reticulum. This new approach shows promise as a tool for future investigation of productive delivery of therapeutic mRNA.